A classification system and analysis for aspect-oriented programs. - Rinard, Martin (Software engineering notes.)
We present a new classification system for aspect-oriented programs. This system characterizes the interactions between aspects and methods and identifies classes of interactions that enable modular reasoning about the crosscut program. We argue that this system can help developers structure their understanding of aspect-oriented programs and promotes their ability to reason productively about the consequences of crosscutting a program with a given aspect. We have designed and implemented a program analysis system that automatically classifies interactions between aspects and methods and have applied this analysis to a set of benchmark programs. We found that our analysis is able to 1) identify interactions with desirable properties (such as lack of interference), 2) identify potentially problematic interactions (such as interference caused by the aspect and the method both writing the same field), and 3) direct the developer's attention to the causes of such interactions.